What is the place of lesbian and bisexual motherhood in school? - Mochi, Luciene Celina Cristina (2022)
The existence of families formed by lesbian and bisexual women challenges compulsory heterosexuality and therefore questions the family model traditionally reproduced by social institutions, especially the school. This binary family composition preserves, as an ideal matrix of family, the model composed by the father, the mother and the children, which perseveres alongside changes and dismemberments that have occurred in family configurations since the 1970s. In this perspective, it is in the school context that the presence of children of lesbian and bisexual mothers breaks the binary logic, while promoting other possibilities of forming families. By considering this debate, this article aims to problematize the place that lesbian and bisexual mothers occupy in the school context. To this end, we organized a bibliographical research based on the Feminist Theories and studies on gender relations. In the final considerations, we present justifications that contribute to scientific research interested in the perspective of relations between school and families.